Cardiac regeneration using human embryonic stem cells: producing cells for future therapy. (September 2010) - Wong, Sharon SY; Bernstein, Harold S
Directed differentiation of human embryonic stem cells (hESCs) has generated much interest in the field of regenerative medicine. Because of their ability to differentiate into any cell type in the body, hESCs offer a novel therapeutic paradigm for myocardial repair by furnishing a supply of cardiomyocytes (CMs) that would ultimately restore normal myocardial function when delivered to the damaged heart. Spontaneous CM differentiation of hESCs is an inefficient process that yields very low numbers of CMs. In addition, it is not clear that fully differentiated CMs provide the benefits sought from cell transplantation. The need for new methods of directed differentiation of hESCs into functional CMs and cardiac progenitors has led to an explosion of research utilizing chemical, genetic, epigenetic and lineage selection strategies to direct cardiac differentiation and enrich populations of cardiac cells for therapeutic use. Here, we review these approaches and highlight their increasingly important roles in stem cell biology and cardiac regenerative medicine.